Cover Image. (22nd February 2022) - Tan, Siyuan; Wang, Juduo; Li, Manli; Yin, Xinchi; Gao, Xiaomei; Li, Chang; Jiang, You; Dai, Xinhua; Gong, Xiaoyun; Fang, Xiang
Abstract : The cover image is based on the Research Article Direct analysis of hydroxylated polycyclic aromatic hydrocarbons in biological samples with complex matrices using polarity‐reversed nanoelectrospray ionization by Siyuan Tan et al., https://doi.org/10.1002/rcm.9237 .